Effect of S. mutans combinations with bifidobacteria/lactobacilli on biofilm and enamel demineralization - Santos, Vanessa Rodrigues Dos [UNESP]; Valdez, Remberto Marcelo Argandoña [UNESP]; Danelon, Marcelle [UNESP]; Souza, José Antonio Santos [UNESP]; Caiaffa, Karina Sampaio [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Duque, Cristiane [UNESP] (FapUNIFESP (SciELO), 2021)
The present study evaluated the ability of Bifidobacterium and Lactobacillus species associated with streptococci to increase insoluble extracellular polysaccharide (EPS) production and initial caries lesion progression. Bovine enamel blocks (n = 190; 4 mm x 4 mm) were prepared, selected according to initial surface hardness (SH), and divided into two groups: a) double combinations: S. mutans with Bifidobacterium or Lactobacillus, and b) triple combinations: S. mutans and S. sobrinus with Bifidobacterium or Lactobacillus species. The blocks were exposed to the bacterial associations for 7 days. Subsequently, quantity of EPS from biofilms and caries lesion depth were determined by means of colorimetric and cross-sectional enamel hardness (ΔKHN) analysis. The data were submitted to one-way analysis of variance, followed by the Bonferroni test (p < 0.05). S. mutans with B. animalis or B. dentium produced a higher quantity of EPS; S. mutans + B. animalis led to the highest ∆KHN. S. mutans + S. sobrinus + B. longum induced greater EPS and ∆KHN values. In conclusion, associations of B. animalis and B. longum with streptococci promoted EPS production and caries lesion progression.